Uji Aktivitas Analgetika Ekstrak Daun Mahang (Macaranga bancana) Terhadap Mencit Putih (Mus musculus L.) Jantan - Mukti, Yusuf Anggoro; Oktavia, Nadia; Andrian, Ine (Jurnal Farmasi & Sains Indonesia, 2024)
According to The International Association for the Study of Pain (IASP) pain is an unpleasant sensory and emotional experience due to damage or threat of tissue damage. When there is damage to body tissue, such as surgery, it will produce damaged cells with the consequence of releasing algesic chemicals that can cause pain. Most clinical guidelines recommend NSAIDs as first-line treatment for pain. The use of NSAID drugs has several side effects including increasing the risk of impaired renal function, bleeding in the gastrointestinal tract, myocardial infarction and stroke. Various side effects caused by using NSAID drugs, then treatment using herbal medicine to treat pain is still an alternative treatment that is expected to have smaller side effects. One plant that is very useful as a medicine is the mahang plant. Based on the results of research, the methanol extract of mahang leaves contains alkaloid, flavonoid, polyphenol and terpenoid/steroid compounds. Flavonoids are secondary metabolite compounds contained in mahang leaf extract which are thought to have pharmacological effects as analgesic agents. The purpose of this study was to evaluate the presence or absence of analgesic activity of mahang leaf extract. This research method is the Tail Flick Test Method using heat as a pain inducer. The administration of mahang leaf extract (Macaranga bancana) to male white mice (Mus musculus L.) can reduce pain due to hot water stimulation as indicated by the extension of the tail flick response time. The optimum concentration of mahang leaf extract that gives analgesic effect is the concentration of mahang leaf extract 400mg/KgBB.